2005
DOI: 10.1002/art.20938
|View full text |Cite
|
Sign up to set email alerts
|

A serum proteomic approach to gauging the state of remission in Wegener's granulomatosis

Abstract: Objective. To identify serum ion patterns that distinguish remission from active disease in patients with Wegener's granulomatosis (WG).Methods. Using sera collected in the WG Etanercept Trial, we selected samples from patients who either were undergoing a period of extended disease remission or had recent flares of active WG. Unfractionated samples were randomized into sets for training and testing, such that remission sera and active disease sera could be analyzed without batch bias. Molecular species within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 31 publications
1
27
0
3
Order By: Relevance
“…The medoid classification algorithm is a best attempt at reproducing the algorithm used in many of the studies conducted in the laboratories of Emmanuel Petricoin and Lance Liotta [Browers et al, 2005;Conrads et al, 2004;Ornstein et al, 2004;Petricoin et al, 2004; www.intechopen.com Srinivasan et al, 2006;Stone et al, 2005]. While these authors stated that their algorithm was quite similar to a Self-Organizing Map (SOM), their algorithm, as they described it, has virtually nothing in common with a SOM.…”
Section: Fingerprint-based Classifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…The medoid classification algorithm is a best attempt at reproducing the algorithm used in many of the studies conducted in the laboratories of Emmanuel Petricoin and Lance Liotta [Browers et al, 2005;Conrads et al, 2004;Ornstein et al, 2004;Petricoin et al, 2004; www.intechopen.com Srinivasan et al, 2006;Stone et al, 2005]. While these authors stated that their algorithm was quite similar to a Self-Organizing Map (SOM), their algorithm, as they described it, has virtually nothing in common with a SOM.…”
Section: Fingerprint-based Classifiersmentioning
confidence: 99%
“…While the algorithm described by Petricoin and Liotta [Browers et al, 2005;Conrads et al, 2004;Ornstein et al, 2004;Petricoin et al, 2004;Srinivasan et al, 2006;Stone et al, 2005] used a genetic algorithm driver to search for an optimum set of features, allowing for different putative solutions to use different numbers of features (5-20 features), our algorithm uses a mEP feature selection algorithm and all putative solutions have the same number of features n. For a given value of n, n features were selected and the intensities of these features were rescaled for each individual using the following formula [Browers et al, 2005;Conrads et al, 2004;Ornstein et al, 2004;Petricoin et al, 2004;Srinivasan et al, 2006;Stone et al, 2005]:…”
Section: Mediod Classification Algorithmmentioning
confidence: 99%
“…As an example, the proteomic analysis of plasma may provide specific profiles for certain kinds of clinical conditions, such as early breast and prostate cancer (Ornstein et al 2004, Martin 2006. A similar approach has been applied to the definition of proteomic signature of the inflammatory status in autoimmune conditions, such as SLE and Wegener's granulomatosis (Bennett et al 2003, Stone et al 2005). …”
Section: The Potential Contribution Of Genomics Transcriptomics and mentioning
confidence: 99%
“…In SLE, microarray analysis of peripheral blood mononuclear cells has allowed the definition of a characteristic expression signature associated with genes regulated by Type I IFN, and this pattern is associated with disease activity (Belmont and Gibbs 2004). Proteomic analysis of biological samples has been also applied to the detection of several types of cancer (Ornstein et al 2004, Liotta andPetricoin 2006) and to the assessment of the activity status of certain inflammatory diseases (Stone et al 2005).…”
Section: The Potential Contribution Of Genomics Transcriptomics and mentioning
confidence: 99%
“…In addition, Stone and colleagues analysed, by mass spectrometry, serum from patients with Wegener's granulomatosis who were enrolled in a trial of the drug etanercept (a TNF inhibitor). They showed that this technique could distinguish between patients in stable clinical remission and those with the active disease 34 . It is important to note that the proteins or peptides identified using unbiased technologies are simply correlated with disease activity, and that their role in disease causation can only be determined through loss-or gain-of-function experiments.…”
Section: Defining the Interactomementioning
confidence: 99%